Feasibility Study on Establishment of TREA Travel Agency Assistance in Lagro Highway, Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
TREA Travel manages every type of travel need, from most uncomplicated to elaborate, and creates an unparalleled experience that customers can rely on. It was built for a purpose, that is, to satisfy the customer’s needs and surpass their expectations. The business offers visa assistance, ticketing, transportation, hotel accommodation, bookings, flight reservation, and cancellations. It is located near Trees Residences and Access College. It is along the highway, and it is accessible for all possible clients. It has 44square meters of commercial rent. The researchers contributed P200,000 each to come up with 1 million pesos as the initial capital. At first, the proponents have had its collaborative brainstorming on what business to be established. An ocular visit to the business site was conducted, followed by a survey for 50 respondents, which included students, employees, and residents, through random sampling. A set of questionnaires was used as instruments for further assessments on the feasibility of establishing the business. Based on the survey, 52% of the respondents are price-sensitive whenever they plan to travel, while 28% of the respondents are looking for fast service. A total of 18% of the respondents were looking for their security identification. Meanwhile, 42% of the respondents are willing to spend between P5,000 and P15,000 for travel packages, while 34% of the respondents can spend between P15,000 and P25,000. A total of 66% chose air transportation as their highest preference for travel assistance, while 18% of the respondents prefer assistance on water transport. Based on the study and findings, the researchers concluded that the TREA Travel Agency Assistance is feasible and viable to the market and offers services locally. REA Travel Agency Assistance will be located at Lagro Highway Novaliches, Quezon City. The target market includes but is not limited to students, employees, and residents in the area. The unit is a commercial space; it has a total length of 11 meters with a width of 4 m. The monthly down payment is P24,000. The Business name represents different meanings; “T” is for travel,“R” is for relaxation, “E” is for enjoyment, and “A” is for adventure. It is a general partnership type of business because everyone wants to experience how to handle a business. All the share assets, profits, financial, and legal liabilities of the company is equal. It also means that the personal assets are liable to the partnership obligation. As global tourism grows yearly, the business has a huge big opportunity for expansion.
Keywords: agency, brainstorming, feasibility, general partnership, hotel, instruments, legal liabilities, mobile app, ticketing, travel, visa